Accuracy and Reliability of 4D-CT and Flexible Laryngoscopy in Upper Airway Evaluation in Robin Sequence. (April 2022) - Lam, Austin S.; Bindschadler, Michael D.; Evans, Kelly N.; Friedman, Seth D.; Blessing, Matthew S.; Bly, Randall; Cunningham, Michael L.; Egbert, Mark A.; Ettinger, Russell E.; Gallagher, Emily R.; Hopper, Richard A.; Johnson, Kaalan; et al.
Objectives: To evaluate the performance of 4-dimensional computed tomography (4D-CT) in assessing upper airway obstruction (UAO) in patients with Robin sequence (RS) and compare the accuracy and reliability of 4D-CT and flexible fiber-optic laryngoscopy (FFL). Study Design: Prospective survey of retrospective clinical data. Setting: Single, tertiary care pediatric hospital. Methods: At initial and 30-day time points, a multidisciplinary group of 11 clinicians who treat RS rated UAO severity in 32 sets of 4D-CT visualizations and FFL videos (dynamic modalities) and static CT images. Raters assessed UAO at the velopharynx and oropharynx (1 = none to 5 = complete) and noted confidence levels of each rating. Intraclass correlation and Krippendorff alpha were used to assess intra- and interrater reliability, respectively. Accuracy was assessed by comparing clinician ratings with quantitative percentage constriction (QPC) ratings, calculated based on 4D-CT airway cross-sectional area. Results were compared using Wilcoxon rank-sum and signed-rank tests. Results: There was similar intrarater agreement (moderate to substantial) with 4D-CT and FFL, and both demonstrated fair interrater agreement. Both modalities underestimated UAO severity, although 4D-CT ratings were significantly more accurate, as determined by QPC similarity, than FFL (−1.06 and −1.46 vs QPC ratings, P = .004). Overall confidence levels were similar for 4D-CT and FFL, but other specialists were significantly less confident in FFL ratings than were otolaryngologists (2.25 and 3.92, P < .0001). Conclusion: Although 4D-CT may be more accurate in assessing the degree of UAO in patients with RS, 4D-CT and FFL assessments demonstrate similar reliability. Additionally, 4D-CT may be interpreted with greater confidence by nonotolaryngologists who care for these patients.